PEMENUHAN ASAS TRANSAKSI SYARIAH PADA PEMBIAYAAN DENGAN AKAD MURABAHAH - Mahmud, Muhammad Daud bin (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2021)
This study aimed to determine the flow of the financing processes with murabahah contract at Bank Syariah Mandiri Branch Office Ternate and to exam whether the financing practices are in accordance with the principles of sharia transactions as stated in Standar Akuntansi Syariahâ€“Indonesian Accounting Standard Board by using qualitative method. The data were collected by using the triangulation sources approach by interviewing a competent banker and a customer, then the results of the interviews are compared with related regulations. The results of this study proved that procedurally the financing processes at Bank Syariah Mandiri Branch Office Ternate has fulfilled the sharia principles, but practically the principle of justice in murabahah contract can not be fulfilled.Â